2023
DOI: 10.1021/acsami.3c04724
|View full text |Cite
|
Sign up to set email alerts
|

Reticulated Polyamide Thin-Film Nanocomposite Membranes Incorporated with 2D Boron Nitride Nanosheets for High-Performance Nanofiltration

Abstract: Nanofiltration (NF) technology has been widely used in saline wastewater treatment due to its unique separation mechanism. However, the NF membrane, as the core of the nanofiltration technology, is restricted by the trade-off between permeability and selectivity, which greatly restricts the development of NF membranes. The interlamellar arrangement of 2D boron nitride nanosheets (BNNSs) can provide additional transport channels and selectivity, as well as strong adsorption capacity due to its high specific sur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 74 publications
1
5
0
Order By: Relevance
“…For the case with the HBPE@PSF synthesized herein, while the HBPE core can form noncovalent CH−π interactions with the BNNS surface, the benzene rings in the PSF side chains can form π–π interactions with the latter. Similar results have also been reported in the literature. , Thus, high-quality BNNSs can be introduced into the composite system via the in situ process, and after the cross-linking via DA reaction, the as-formed hyperbranched-star, reversibly cross-linking structure can further join tightly them together to form effective thermal transfer paths, thus imparting the resultant composite adhesives with excellent interfacial thermal transfer performance (Figure d).…”
Section: Resultssupporting
confidence: 86%
“…For the case with the HBPE@PSF synthesized herein, while the HBPE core can form noncovalent CH−π interactions with the BNNS surface, the benzene rings in the PSF side chains can form π–π interactions with the latter. Similar results have also been reported in the literature. , Thus, high-quality BNNSs can be introduced into the composite system via the in situ process, and after the cross-linking via DA reaction, the as-formed hyperbranched-star, reversibly cross-linking structure can further join tightly them together to form effective thermal transfer paths, thus imparting the resultant composite adhesives with excellent interfacial thermal transfer performance (Figure d).…”
Section: Resultssupporting
confidence: 86%
“…After DMSN embedment, the thicknesses for PAN–DMSNs 50 –PA, PAN–DMSNs 100 –PA, and PAN–DMSNs 150 –PA membranes decrease to 199, 134, and 146 nm, respectively. It was reported that nanomaterials on the substrate could regulate the IP process and reduce the thickness of the PA layer. , For PAN–DMSNs–PA membranes, the embedded DMSNs could store PIP molecules via hydrogen bonds and electrostatic interaction, controlling the release of PIP toward the interfacial reaction zone. Therefore, the thickness of PAN–DMSNs–PA membranes is lower than that of the PAN–PA membrane.…”
Section: Resultsmentioning
confidence: 99%
“…(A) Water permeance and (B) salt rejection of TFC and TFC-M/C 0.5 membranes, (C) separation performance of TFC-M/C 0.5 membrane for different heavy metal salts, (D) rejection of different heavy metal ions in actual textile wastewater of TFC and TFC-M/C 0.5 membranes, (E) long-term stability of the TFC-M/C 0.5 membrane, and (F) comparisons of the permeance and selectivity coefficient of Na 2 SO 4 /NaCl of TFC-M/C 0.5 membrane with various reported NF membranes. ,,,,,, …”
Section: Resultsmentioning
confidence: 99%